Visuomotor Adaptation Brain Changes During a Spaceflight Analog With Elevated Carbon Dioxide (CO2): A Pilot Study - Salazar, Ana Paula; Hupfeld, Kathleen E.; Lee, Jessica K.; Banker, Lauren A.; Tays, Grant D.; Beltran, Nichole E.; Kofman, Igor S.; De Dios, Yiri E.; Mulder, Edwin; Bloomberg, Jacob J.; Mulavara, Ajitkumar P.; Seidler, Rachael D. (Frontiers in Neural Circuits, 2021)
Astronauts onboard the International Space Station (ISS) must adapt to several environmental challenges including microgravity, elevated carbon dioxide (CO2), and isolation while performing highly controlled movements with complex equipment. Head down tilt bed rest (HDBR) is an analog used to study spaceflight factors including body unloading and headward fluid shifts. We recently reported how HDBR with elevated CO2 (HDBR+CO2) affects visuomotor adaptation. Here we expand upon this work and examine the effects of HDBR+CO2 on brain activity during visuomotor adaptation. Eleven participants (34±8 years) completed six functional MRI (fMRI) sessions pre-, during, and post- HDBR+CO2. During fMRI, participants completed a visuomotor adaptation task, divided into baseline, early, late and de-adaptation. Additionally, we compare brain activity between this NASA campaign (30-day HDBR+CO2) and a different campaign with a separate set of participants (60-day HDBR with normal atmospheric CO2 levels, n = 8; 34.25 ± 7.9 years) to characterize the specific effects of CO2. Participants were included by convenience. During early adaptation across the HDBR+CO2 intervention, participants showed decreasing activation in temporal and subcortical brain regions, followed by post- HDBR+CO2 recovery. During late adaptation, participants showed increasing activation in the right fusiform gyrus and right caudate nucleus during HDBR+CO2; this activation normalized to baseline levels after bed rest. There were no correlations between brain changes and adaptation performance changes from pre- to post HDBR+CO2. Also, there were no statistically significant differences between the HDBR+CO2 group and the HDBR controls, suggesting that changes in brain activity were due primarily to bed rest rather than elevated CO2. Five HDBR+CO2 participants presented with optic disc edema, a sign of Spaceflight Associated Neuro-ocular Syndrome (SANS). An exploratory analysis of HDBR+CO2 participants with and without signs of SANS revealed no group differences in brain activity during any phase of the adaptation task. Overall, these findings have implications for spaceflight missions and training, as ISS missions require individuals to adapt to altered sensory inputs over long periods in space. Further, this is the first study to verify the HDBR and elevated CO2 effects on the neural correlates of visuomotor adaptation.